The Role of Personal Branding in Shaping Consumer Purchasing Decisions: A Systematic Literature Review - Khoirun Nisa Bahri; Ahmad Johan; Vanessa Gaffar (Al-Qalam Institue, 2026)
This study aims to examine the role of personal branding in influencing consumer purchasing decisions in the digital business environment. The research employs a systematic literature review (SLR) by analyzing relevant scholarly publications on personal branding and consumer purchasing behavior. The reviewed literature was selected based on predefined inclusion and exclusion criteria to ensure the relevance and quality of the findings. The results indicate that personal branding has a significant positive influence on purchasing decisions by enhancing credibility, trust, perceived value, and consumer engagement. Strong personal branding also increases consumers' confidence in products and strengthens purchase intentions across digital platforms. Furthermore, the findings suggest that personal branding has evolved into an essential competency for professionals, entrepreneurs, and business practitioners seeking to improve market competitiveness and establish long-term relationships with consumers. The study implies that organizations and individuals should strategically develop authentic and consistent personal branding to enhance consumer trust and support sustainable business performance in the digital era.